Business Demand And Skill Specifications For Data Analysts In Indonesia: A Data-Driven Job Market Study - Koswara, Asep (Politeknik Kebangsaan, 2025)
Indonesia’s accelerated digital transformation has generated a substantial demand for data analysts, yet a fine-grained understanding of sector-specific hiring trends and skill requirements remains limited. This study addresses that gap by conducting a data-driven job market analysis of 100 New Data Analyst postings collected from JobStreet Indonesia. Using quantitative content analysis and computational techniques, the research classified postings by business sector and extracted explicit skill requirements, encompassing both technical and soft competencies. The findings reveal that demand is most concentrated in e-commerce, finance, healthcare, and technology, with Jakarta emerging as the dominant employment hub. Technical skills such as SQL, Python, Excel, and visualization tools remain foundational across sectors, while sectoral variations highlight specialized needs, including risk modeling in finance and consumer analytics in e-commerce. Equally important, soft skills such as communication, problem-solving, and adaptability are consistently emphasized, underscoring the hybrid nature of the role. These results suggest that employers, job seekers, and educators must collaboratively align expectations, training programs, and recruitment practices to minimize skill mismatches. The study concludes by recommending competency-based curricula, industry-academia partnerships, and continuous upskilling strategies to ensure Indonesia’s workforce is adequately prepared to meet the evolving demands of the digital economy.